"A disease that God has given me" patients and caregivers' perspectives on diabetes in southeastern Tanzania - Emmy Metta (BMC, 2023)
Abstract Background Prompt diagnosis and appropriate management of diabetes has the potential of improving survival and patient health outcomes. Yet many diabetes patients present themselves to health facilities at an advanced stage of the disease which complicates its management. Individual perceptions about diseases are known to play a critical role in informing responses and actions including seeking health care and self-care practices. However, little is documented in Tanzania regarding the perspectives of diabetes patients and their caregivers about the disease especially in rural settings. Methods We conducted 26 in-depth interviews involving 19 diabetes patients and 7 diabetes patient caregivers to explore in detail their perspectives on diabetes as a disease. Data was analyzed using thematic analysis with the help of NVivo9. Results Both patients and caregivers expressed mixed perceptions on diabetes causes. In addition to heredity, and the failure of the pancreas to function well, lifestyle factors including lack of physical activity and eating too many sugary and oily foods were common reported causes. However, none of the participants were clear on the mechanisms between the perceived causes and the actual occurrence of the disease. Perception on susceptibility to diabetes was low even among participants with the disease as they reported not having ever thought of getting the condition before they were diagnosed. Some caregivers expressed worry and fear on their susceptibility to inheriting diabetes from their relatives who had the condition. Diabetes was perceived as a severe and life-threatening condition that can easily cause death if not well managed. Participants indicated uncertainty on its prevention. Conclusion This study shows mixed perspectives on the causes, susceptibility, severity and prevention of diabetes which were informed by the participants' limited knowledge and awareness about the disease. Interventions to strengthen responses to diabetes, which include buy-in from the patients and their caregiver's perspectives are essential to improve prevention, early diagnosis and appropriate management in rural settings.